2022
DOI: 10.1111/ijlh.14010
|View full text |Cite
|
Sign up to set email alerts
|

Additional value of red blood cell parameters in predicting uncommon α‐thalassemia; experience from 10 years of α‐globin gene sequencing and copy number variation analysis

Abstract: Introduction The diagnosis of rare forms of α‐thalassemia requires laborious genetic analyses. Accurate sample selection for such evaluation is therefore essential. The main objectives of this study were to investigate the predictive power of red blood cell parameters to detect rare forms of α‐thalassemia (substudy 1), and to explore the frequency of rare versus common forms of α‐thalassemia in our sample population (substudy 2). Methods In substudy 1, we reviewed all blood samples selected for extended α‐hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The results showed that RBC, MCV, RDW-CV, and RDW-SD had statistical significance and were independent risk factors for distinguishing ABO neonatal hemolytic disease from other non-neonatal hemolytic disease hyperbilirubinemia. Specifically exhibited a significant positive association with a substantial 261.8% increase in the risk of hemolytic diseases also contributing to the differential diagnosis of another disease, such as Hepatitis B Virus-related chronic liver diseases [ 22 ] and α-thalassemia [ 23 ]. In contrast, ABO blood type and WBC count were not significant predictors of hemolytic disease in multivariate analyses [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that RBC, MCV, RDW-CV, and RDW-SD had statistical significance and were independent risk factors for distinguishing ABO neonatal hemolytic disease from other non-neonatal hemolytic disease hyperbilirubinemia. Specifically exhibited a significant positive association with a substantial 261.8% increase in the risk of hemolytic diseases also contributing to the differential diagnosis of another disease, such as Hepatitis B Virus-related chronic liver diseases [ 22 ] and α-thalassemia [ 23 ]. In contrast, ABO blood type and WBC count were not significant predictors of hemolytic disease in multivariate analyses [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%